The Retinal Oxygen Saturation Measured by Dual Wavelength Oximetry in Larger Retinal Vessels is Influenced by the Linear Velocity of the Blood. (2nd January 2019) - Jeppesen, Signe Krejberg; Bek, Toke
ABSTRACT: Purpose: Dual wavelength retinal oximetry allows the quantification of oxygen saturation in the larger retinal vessels. However, the technique might be refined further by identifying factors that are responsible for the different oxygen saturations in first order arterioles from the same eye shortly after their branching from the central retinal artery. The purpose of the present study is to investigate whether these factors involve rheological characteristics in the studied vessels. Materials and Methods: In fourty healthy persons the oxygen saturation was measured by dual wavelength oximetry and the blood flow by Doppler OCT in the upper and lower temporal and nasal arterioles and venules shortly after their branching from the central retinal artery and vein. The relationship of the measured oxygen saturations with age, vessel diameter, and blood linear velocity were assessed. Results: The measured oxygen saturations were (mean± SD) 97.8% ± 6.4% in the arterioles and 60.2% ± 8.8% in the venules. For both the arterioles and the venules the measured oxygen saturation (Sm ) correlated significantly with the linear velocity (v) of the blood in mm/s (Sm  = 101.6–0.28*v, p  < 0.0001 for arterioles and Sm  = 64.5–0.38*v, p  = 0.002 for venules). After correction for the variation in linear velocity, the differences in saturation between first order branches from both arterioles and venules were significantly reduced and the standard deviation of the oxygen saturations were reduced to less than one third. Conclusions: Measurements of oxygen saturation in larger retinal arterioles and venules using dual wavelength oximetry can be improved by correcting for the influence of the linear velocity of the blood.